Tomato Production under Synergistic Application of Phosphate Solubilizing Bacteria and Phosphate Amendments - Dereje Haile; Bizuayehu Tesfaye; Fassil Assefa (Advances in Agriculture)
Phosphate solubilizing bacteria have multi-dimensional benefits in broad host range interaction, accessing nutrients, phytohormone induction, stress alleviation, biocontrol activity, and eco-friend approach. This study aimed to evaluate the efficacy of PSB isolates coinoculated with compost, bone meal, and DAP fertilizer on tomato growth response. Tomato seeds were treated with 10 selected PSB isolates separately and grown for 20 days on seedbed, then transplanted to field that was treated with external P-sources and enriched by PSB inoculum. PSB isolates showed positive interaction and achieved significant plant assays including plant height, leaves, branches, flowers, and fruit development. Isolate K-10-41 significantly promoted tomato plant height, floral development, and fruit yield, Mk-20-7 enhanced height and fruit weight whereas K-10-27 induced tomato fruit numbers. Compost application promoted tomato-PSB interaction and induced tomato vegetative growth whereas bone meal was least promotor for most of tomato plant assays. Bone meal was however, one of the top fruit development inducers (harvested 20.94 fruits/plant weighing 881.97 gm). Mixing 50% of recommended compost and DAP fertilizer application enhanced tomato vegetative growth and fruit yield (21 fruits/plant harvested that weighed 872.46 gm). Based on the overwhelming performance, K-10-41 and Mk-20-7 application together with compost and fertilizer mixture were found effective. Therefore, the results of this study imply that application of competent PSB isolates together with nutrient supplements improved symbiotic effectiveness, sustainable production, and environmental health. Consequently, these promising isolates would be recommended for tomato production of higher yield and sustainability after verifying their efficacy at different agroecology and taxonomic identification. Screening potential strains and evaluating their competence under different conditions would be the future perspectives to develop efficient inoculants. Moreover, synergetic application of organic supplements (compost, farmyard, bone meal, or other biowastes), bioinoculants, and proper agrochemicals maximize production and environmental health and is feasible for the economic, social, and ecological sense of balance.